The Influence of Locally Generated Revenue, Public Allocation Funds and Specific To Financial Performance of The Region in The City/Regency Government in Aceh Province - Zainal Putra (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2016)
The purpose of this research are: (1). To know how the condition of region own source revenue, the general allocation fund, special allocation fund and regional financial performance , (2). To find out the influence of region own source revenue, the general allocation fund, special allocation fund to the region financial performance, (3). To know the influence of region own source revenue to the region financial performance, (4). To find out the influence of the general allocation fund to the region financial performance, (5). to know the effect of the special allocation fund toward region financial performance. The data used in this research is a secondary data obtained from the office of BPK RI Aceh province Representative. The data collected in the form of pooling data in period of 2008-2012. The entire population in this research are sampled as many as 23 regencies / cities in Aceh province. In analyzing the data using multiple linear regression models. The results showed that: (1). Regencies / cities in Aceh province the category of of region finance ability is “very less